Meta-QTL s and haplotypes for efficient zinc biofortification of rice - Joshi, Gaurav; Soe, Yan Paing; Palanog, Alvin; Hore, Tapas Kumer; Nha, Chau Thanh; Calayugan, Mark Ian; Inabangan-Asilo, Mary Ann; Amparado, Amery; Pandey, Indra Deo; Sta. Cruz, Pompe C.; Hernandez, Jose E.; Swamy, B.P. Mallikarjuna (Wiley, 2023)
Biofortification of rice with improved grain zinc (Zn) content is the most sustainable and cost‐effective approach to address Zn malnutrition in Asia. Genomics‐assisted breeding using precise and consistent Zn quantitative trait loci (QTLs), genes, and haplotypes can fast‐track the development of Zn biofortified rice varieties. We conducted the meta‐analysis of 155 Zn QTLs reported from 26 different studies. Results revealed 57 meta‐QTLs with a significant reduction of 63.2% and 80% in the number and confidence interval of the Zn QTLs, respectively. Meta‐quantitative trait loci (MQTLs) regions were found to be enriched with diverse metal homeostasis genes; at least 11 MQTLs were colocated with 20 known major genes involved in the production of root exudates, metal uptake, transport, partitioning, and loading into grains in rice. These genes were differentially expressed in vegetative and reproductive tissues, and a complex web of interactions were observed among them. We identified superior haplotypes and their combinations for nine candidate genes (CGs), and the frequency and allelic effects of superior haplotypes varied in different subgroups. The precise MQTLs with high phenotypic variance, CGs, and superior haplotypes identified in our study are useful for an efficient Zn biofortification of rice and to ensure Zn as an essential component of all the future rice varieties through mainstreaming of Zn breeding.